IP Subnet Based Vlan: Issues, Protocol, Implementation And Solutions - Chan , Wai Kok (2002)
The main objectives of VLAN(Virtual Local Area network) are broadcast isolation as well as simplification of processes of addition, movement or changes. Even though IP subnet VLAN is a common feature in Ethernet switches today, many of its implementationdetails are not fully known because generally the vendors do not describe it. This thesis therefore presents a study of an implementation of a simple IP subnet VLAN. The four main issues discussed in this thesis are broadcast traffic trend, frame classification, inter-switch VLAN Registration Protocol and efficient routing. After analysing the traffic in few LANs, it was discovered in this work that the broadcast traffic is generally very low and VLAN is of little use for broadcast isolation. Amazingly, it was found that if a router sends a multicast VLAN frame to all switches periodically, then no VLAN registration protocol is actually required in any of the switches. However , in this case the broadcast traffic is unnecessarily extended to a larger part of the network. Though an intelligent broadcast isolation method can remove this problem, all the switches are now required to run some form of VLAN registration protocol in order for the VLAN to function properly. Thus, the implementers have to choose between unnecessary extension of broadcast traffic or having to run a VLAN registration protocol. A switch must be able to classify frames into its relevant VLAN before any kind of VLAN filtering can be done. A list of all the possible frames are generated and verified in this work to ensure that the frame classification process encompassed all possible frame combinations. A network demonstrating how switches exchange VLAN membership information between each other is implemented and fully tested in this work. Various methods have also been proposed to improve the amount of time needed for learning of a new VLAN or for removing it from the network. In order for the VLAN to function correctly , each switch needs to have two VLAN filtering database. When a switch detects a new VLAN via frame classification process, a multicast VLAN frame will be sent to all the switches so that the network can learn it immediately. A VLAN ID can be quickly removed from the network by synchronising each switch to send a VLAN frame at a slightly later interval that is very close to each other. In this way, the neighbouring switches will send out the VLAN frame almost immediately after receiving it as it has reached its VLAN transmission interval. This has been verified from results obtained from simulation. It is known that many existing VLAN implementations have some inefficiency when it comes to IP routing. Therefore in this thesis, an efficient IP routing mechanism is implemented and tested. Simulation results prove that this new routing mechanism is more efficient than conventional one arm routing in most of the network configurations.